Hubungan antara Faktor Maternal dengan Kejadian Bayi Stunting 0-6 bulan di Kabupaten Asmat Provinsi Papua - Veronica, Yustitio Nora; Purba, Ambrosius; Anwar, Anita Deborah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
ABSTRACT This research was motivated by the issue of the incidence of stunting in infants aged 0-6 months in Asmat Regency, Province of Papua. Stunting is a growth disorder that occurs due to chronic malnutrition and / or chronic infectious conditions so that the body's condition becomes short and very short to exceed the deficit-2SD below the median length or height. Chronic malnutrition and chronic infectious diseases are allegedly related to maternal factors. This study was an observational analytic study with a case-control study design in 146 respondents divided into 2 groups. The case group consisted of 73 mothers who had a stunting baby aged 0-6 months and the control group consisted of 73 mothers who had a non-stunting baby aged 0-6 months. This research was conducted in Asmat Regency, Province of Papua for 2 months using a questionnaire checklist. To determine the relationship of maternal factors to the incidence of stunting used the Chi-Square Test and the Double Logistic Regression Analysis test. Correlation test results between the nutritional status factors of breastfeeding mothers with the incidence of stunting infants aged 0-6 months was p = 0.001, the relationship of the age factor of the first pregnant mother with the incidence of stunting infants aged 0-6 months was p = 0.001, and the relationship between disease history during pregnancy with the incidence of stunting infants aged 0-6 months is p=0.00. The results of multiple logistic regression analysis showed the factors of comorbidities during pregnancy had a strong influence OR = 67.64 on the incidence of stunting infants aged 0-6 months and nutritional status factors of breastfeeding mothers also had a strong influence OR = 6,392 on the incidence of stunting infants aged 0-6 months. The results of this study indicate that maternal factors: factors nutritional status of breastfeeding mothers, the age factor of the first pregnant woman, and a history of comorbidities during pregnancy have a relationship with stunting infants aged 0-6 months, but who have the most strong influence on the incidence of stunting infants 0-6 months is a history of comorbidities during pregnancy and nutritional status of nursing mothers.